2012
DOI: 10.3892/or.2012.1723
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 and CpG oligonucleotide therapy suppresses the outgrowth of tumors by activating tumor-specific Th1-type immune responses

Abstract: Abstract. Because IL-4 and CpG oligodeoxynucleotides (CpG-ODNs) are immune stimulants, we evaluated the antitumor effects of IL-4 gene therapy and CpG-ODN treatment in a poorly immunogenic murine cancer model. We used a murine colorectal cancer MC38 cell line overexpressing the IL-4 gene (MC38-IL4). Incubation with MC38-IL4 and CpG-ODN enhanced bone marrow-derived dendritic cell (DC) maturation in vitro. In addition, interferon (IFN)-γ production was significantly increased in naïve splenocytes after they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…In this regard, cytotoxic T lymphocytes (CTLs) play a central role in the immunosurveillance and clearance of both intracellular pathogens and malignant cells (20,21). On the other hand, Th1 cells play a critical role in the immune system's challenge with tumors (22). Some studies also indicated the importance of dendritic cells (DCs) as APC for presenting tumor antigens to CTLs or CD4 + T cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, cytotoxic T lymphocytes (CTLs) play a central role in the immunosurveillance and clearance of both intracellular pathogens and malignant cells (20,21). On the other hand, Th1 cells play a critical role in the immune system's challenge with tumors (22). Some studies also indicated the importance of dendritic cells (DCs) as APC for presenting tumor antigens to CTLs or CD4 + T cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…IL4 also plays a pivotal role in antibody isotype switching and stimulates the production of IgE. This cytokine has been applied in the treatment of autoimmune disorder like multiple myeloma [3], cancer [4], psoriasis [5], and arthritis [6]. IL4 has also been extensively applied to inhibit detrimental effect of Th1 [7].…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest an intriguing duality of IL4 function; host-derived IL4 seems to contribute to tumor control, while tumor-derived IL4 contributes to tumor growth. Other groups have investigated the role of tumor-derived IL4 in shaping the TME and impacting tumor growth, however, these models involved expression of IL4 under control of viral promoters that results in supraphysiological levels of IL4 (37, 38). In contrast, we provide the first reported insight into the relative contribution of host- versus tumor-derived IL4 using a model system that expresses endogenous levels of IL4.…”
Section: Discussionmentioning
confidence: 99%